Perspectives on development in Arid and Semi-Arid areas: Results of a ranking exercise - McPeak, J.G.; Gebru, G.; Lemunyete, R.; Kristjanson, Patricia M. (International Livestock Research Institute, 2006)
Decentralization and community participation are major themes in current development policy. This study investigates perspectives on development held by individuals in arid and semi-arid areas of northern Kenya and southern Ethiopia that are predominantly used for pastoral production. Using a ranking exercise, individuals were asked to identify the most helpful types of development interventions in their opinion in the past, and also indicate their priorities for future development interventions. Results suggest there is relative consensus around a few key development interventions. Interestingly, the highest ranked interventions for both the past and the future are not explicitly related to pastoral production. Across country differences are not very large, though across site differences are pronounced. In a similar fashion, individual characteristics seem to matter less than household level characteristics within sites.